Neoliberal Narrative in Times of Economic Crisis: A Political Claims Analysis of the U.K. Press, 2007‐14. Issue 3 (14th June 2016) - Temple, Luke; Grasso, Maria T.; Buraczynska, Barbara; Karampampas, Sotirios; English, Patrick
Abstract : Using political claims analysis on 1, 000 articles from five national newspapers ( Daily Mail, The Sun, The Times, The Guardian, and Daily Mirror ), this article demonstrates that press coverage of the financial crisis, recession, and austerity in the United Kingdom between 2007‐14 drew heavily on a neoliberal discourse. Political, market, and civil society actors discussed the impact of hard times on people using a reductionist neoliberal narrative, framing people as "economic actors" and consistently underplaying any social or political traits. By examining communicative, rather than coordinative, discourse this research expands the focus of previous studies which have examined the embeddedness of ideology in society, and highlights potential links to studies of citizen participation and mobilization. Related Articles in this Special Issue: Cinalli, Manlio, andMarco Giugni .2016 . "Collective Responses to the Economic Crisis in the Public Domain: Myth or Reality? "Politics & Policy 44 (3 ): 427–446.http://onlinelibrary.wiley.com/doi/10.1111/polp.12159/abstract Giugni, Marco, andMaria T. Grasso .2016 . "How Civil Society Actors Responded to the Economic Crisis: The Interaction of Material Deprivation and Perceptions of Political Opportunity Structures ."Politics & Policy 44 (3 ): 447–472.http://onlinelibrary.wiley.com/doi/10.1111/polp.12157/abstract English, Patrick, Maria T. Grasso, Barbara Buraczynska, Sotirios Karampampas, andLuke Temple .2016 . "Convergence on Crisis? Comparing Labour and Conservative Party Framing of the Economic Crisis in Britain, 2008‐14 ."Politics & Policy 44 (3 ): 577–603.http://onlinelibrary.wiley.com/doi/10.1111/polp.12160/abstract Related Media: Youtube .2015 . "Neoliberalism's Stealth Revolution ‐ Interview with Wendy Brown."https://www.youtube.com/watch?v=sUGSjd_OoQ0 LSE British Politics and Policy Blog .2016 . "Words Matter: Deconstructing 'Welfare Dependency' in the UK – Paul Michael Garrett."http://blogs.lse.ac.uk/politicsandpolicy/%EF%BB%BFwords-matter-deconstructing-welfare-dependency-in-the-uk/